THE INFLUENCE OF LEARNING MODEL BASED CHARACTER EDUCATION TO STUDENT CHARACTERS AND LEARNING OUTCOMES - ., Derlina; Mihardi, Satria; ., Sabani (Advances in Social Sciences Research Journal, 2016)
This research objective is to know the influence of learning model based character education to students learning outcome in cognitive domain in general physics I subject and the characters that can be developed. This research used quasi experiment method, the population are all of the students in mathematics education science faculty in State University of Medan that attend the general physics I subject, with sample of two classes. One class is experimental class that treatment by learning model based characters, the other one is control class without learning model based characters. Through this model also developed the character of interpersonal and intrapersonal students. Interpersonal character involve the religious aspect, curiosity, responsibility, thoroughness, perseverance, honesty and confidence and intrapersonal characters involve aspects of cooperation and tolerance. The conclusion is that there is the influence of learning model based characters education to students learning outcomes in cognitive domain, where the cognitive learning outcomes of students that learned by the learning model based character education is higher than that learned without learning model based character education